STATISTIC STUDY REGARDING THE ARDS USING IMPLANTS ACCORD WITH CLINICAL CASES PARTICULARITIES - Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2014)
The oral rehabilitation represents that integrative concept which re-establishes each segment of the stomatognat system, affected by edentation with different clinical forms, without eluding the induced complications and the influence which such a general state has within the selected therapy algorithm. The aim of this study is to evaluate the election therapeutic solution during the rehabilitation of particularly type of edentulous, identifying the causes which lay at the basis of failure, as well as the required support, multiple factorial which lies at the basis of the successful clinical verdict according with the particularities of the implants type